Limited liability partnerships: its emergence in Southeast Asia - Abd Ghadas, Zuhairah Ariff (2010)
A business entity is basically a structure which is recognized by the law as a valid medium to carry on trade. Globally, there are many types of business entities but the common business entites which are practiced all over the world are the sole proprietorship, partnerships (firm) and companies. In Malaysia, these three are the only business structure which is offered in the market place. In many other countries, business entities have been expanded and developed to cater the business needs. One of the latest inventions of business entity is the limited liability partnerships (LLPs). LLP is a fascinating business structure as it could have the status of either a legal entity which is not a body corporate or a body corporate. In the United Kingdom, for example, the off shores LLPs, such as the Isle of Jersey LLPs have the status of a legal entity which is not a body corporate whilst in the mainland; the UK LLPs have the status of a body corporate. In the South East Asia region, at present LLPs is only available in Selangor. In Malaysia, there is a positive indication towards introducing LLPs in the near future as the Companies Commission of Malaysia (CCM) had recently published the consultation documents on LLP (April 2009). This paper intends to discuss features of LLPs as a new business entity and as the latest creation of a body corporate. Special reference is made to the Jersey LLPs and the UK LLPs to highlight different types of LLPs structure and also to the Singapore LLP Act 2005 and the Companies Commission of Malaysia (CCM) consultation documents on LLP (April 2008) to underline the attributes of LLPs which are available in the South East Asia.